Safer insulin needle use and disposal - Furth, Rebecca; Audrey, Anderson; Gumti, Krishendat (International Journal of Infection Control, 2009)
The safe use and disposal of injection equipment is a major component of infection control in clinical and community settings. Diabetic insulin users represent a significant population of injection equipment consumers whose practices have implications for community safety. Most insulin users inject at home; yet even in developed countries, there are few options for safely disposing of needles or lancets in the home setting. This paper presents the results of a pilot program designed to test out low cost, practical options for improving insulin syringe use and disposal safety in Guyana. The Pilot tested out the provision of a full monthly supply of insulin syringes to try and address re-use, trialed four different containers to contain used needles at home and return them to health facilities for disposal, and included training for diabetes clinic nurses and pharmacists in client counseling and waste handlers in the disposal of insulin syringes containers returned to facilities by clients. The Pilot found that, with training, nurses and pharmacists were able to counsel clients successfully. Insulin needle re-use declined from 87% to 8% with the provision of full supply and clients felt safer using a single needle for each injection, disposing used syringes into containers and returning full containers facilities for disposal. All disposal containers worked well with no punctures or leakages, but used tablet containers and client sourced containers are the most sustainable in the Guyana context because they carry no additional cost and are readily available.